Vintage approach to forecasting palm oil production in Peninsular Malaysia - Ali Nordin, Ali Zulhusni; Ahmad, Siti Mashani; Mohamed Arshad, Fatimah; Mohd Noh, Kusairi; Mohamed, Zainal Abidin; Alias, Emmy Farha; Ng, Keng Yap; Idris, Nurjihan; Jabir, Nur Alina (Malaysian Palm Oil Board, 2014)
Oil palm is an important crop to the Malaysian economy. Due to its strategic significance there is a need to have a reliable estimate of the production of the commodity to facilitate decision-making by policymakers and industry participants. The vintage approach has been shown to be more efficient in taking into account the age of palms and their yield profile when estimating production compared with other methods. The study utilised the vintage approach adapted from Smit (2010). The findings suggest that the vintage model developed is capable of projecting as well as simulating the impact on the palm oil sector if a change or shock is injected into the system.